Vjersko vs. sekularno / Religious vs. Secular: Sudstvo u šerijatskom, jevrejskom i Common Law pravu / Judiciary in Sharia, Jewish and Common Law Legal System (Pregled: časopis za društvena pitanja / Periodical for social issues, 2021)
This text is the review of a book Courts: Comparative Study by Ehlimana Memišević (Center for Advaced Studies, 2019).